Improved uniformity in the switching characteristics of ZnO-based memristors using Ti sub-oxide layers. (23rd November 2016) - Park, Ju Hyun; Jeon, Dong Su; Kim, Tae Geun
Abstract: In this paper, improved uniformity in the resistive switching (RS) characteristics of ZnO-based memristors using Ti sub-oxide layers (metallic TiO x, insulating TiO y ) is reported. Compared with Pt/Ti/ZnO/Pt cells, more reliable and reproducible RS operation was observed in Pt/TiO x (or TiO y )/ZnO/Pt cells, particularly with insulating TiO y, because Ti sub-oxide layers play the role of oxygen reservoirs that help rupture the conducting filament. By comparison, Pt/TiO y /ZnO/Pt cells exhibited the best performance, with a large on/off ratio (~10 5 ) at a read voltage of 0.4 V, and highly stable low- and high-resistive state operation for 100 direct-current sweep cycles.